High frequency percussive ventilation for respiratory immobilization in radiotherapy. (March 2019) - Sala, Ina M.; Nair, Girish B.; Maurer, Beverly; Guerrero, Thomas M.
Highlights: HFPV maybe a tool for immobilizing thoracic targets in radiotherapy. The procedure itself was well tolerated and well complied. Chest wall motion was significantly reduced by greater than 60%. HFPV can be greatly advantageous, particularly for SBRT and PBS proton therapy. Duty cycle under HFPV was significantly higher than conventional methods. The appropriate interface can lead to extensive HFPV prolonged times. Abstract: High frequency percussive ventilation (HFPV) employs high frequency low tidal volumes (100–400 bursts/min) to provide respiration in awake patients while simultaneously reducing respiratory motion. The purpose of this study is to evaluate HFPV as a technique for respiratory motion immobilization in radiotherapy. In this study fifteen healthy volunteers (age 30–75 y) underwent HFPV using three different oral interfaces. We evaluated each HFPV oral interface device for compliance, ease of use, comfort, geometric interference, minimal chest wall motion, duty cycle and prolonged percussive time. Their chest wall motion was monitored using an external respiratory motion laser system. The percussive ventilations were delivered via an air driven pneumatic system. All volunteers were monitored for PO2 and tc-CO2 with a pulse oximeter and CO2 Monitoring System. A total of N = 62 percussive sessions were analyzed from the external respiratory motion laser system. Chest-wall motion was well tolerated and drastically reduced using HFPV in each volunteer evaluated. As a result, we believe HFPV may provide thoracic immobilization during radiotherapy, particularly for SBRT and pencil beam scanning proton therapy.